Temporal Relationship Between Particulate Matter (PM 10) And Sulphur Dioxide (SO2) In Developing Town In North Malaysia - Awangku Ibrahim, Dayangku Kamisah (Universiti Sains Malaysia, 2005)
Quality of air is a very important component to human beings, animals and plants. But, nowadays air has become polluted seriously and the amount of the air pollutants increasing in the air. There are many types of air pollutants such as carbon monoxide, nitrogen dioxide, hydrocarbon, sulphur dioxide and particulate matter. These air pollutants are contributed by many sources such as motor vehicles, industry, and open burning. The scope of this research is about particulate matter up to 10µm and sulphur dioxide in Prai, Pulau Pinang. Prai is one of the industrial areas in Malaysia and this sector contributed large effect to the pollution of this area. These studies are done on the concentration of particulate matter (PM10) by analysis the data from January till August and for sulphur dioxide (SO2) the data given from January till Jun. For PM10 the mean values ranging from 61µg/m³ up to 93µg/m³, maximum value is 540µg/m³ and minimum value is 7µg/m³ and for SO2 the mean values ranging from 0.014 ppm up to 0.025 ppm, maximum value is 0.147 ppm and minimum value is 0 ppm. The value of correlation (r²) between PM10 and SO2 is 0.0097 for weekdays and 0.2927 for weekends which indicates that there is poor correlation between PM10 and SO2.